Characterization of CobB kinetics and inhibition by nicotinamide - Gallego-Jara, Julia (PLoS One, 2017)
Lysine acetylation has emerged as a global protein regulation system in all domains of life. Sirtuins, or Sir2-like enzymes, are a family of histone deacetylases characterized by their employing NAD(+) as a co-substrate. Sirtuins can deacetylate several acetylated proteins, but a consensus substrate recognition sequence has not yet been established. Product inhibition of many eukaryotic sirtuins by nicotinamide and its analogues has been studied in vitro due to their potential role as anticancer agents. In this work, the kinetics of CobB, the main Escherichia coli deacetylase, have been characterized. To our knowledge, this is the first kinetic characterization of a sirtuin employing a fully acetylated and natively folded protein as a substrate. CobB deacetylated several acetyl-CoA synthetase acetylated lysines with a single kinetic rate. In addition, in vitro nicotinamide inhibition of CobB has been characterized, and the intracellular nicotinamide concentrations have been determined under different growth conditions. The results suggest that nicotinamide can act as a CobB regulator in vivo. A nicotinamidase deletion strain was thus phenotypically characterized, and it behaved similarly to the ΔcobB strain. The results of this work demonstrate the potential regulatory role of the nicotinamide metabolite in vivo.